Social psychology: new directions in computer-based learning - Lesley J. Allinson (Association for Learning Technology, 1996)
Perhaps surprisingly, psychology has been a discipline eager to capitalize on the application of computers for teaching. Traditionally, this has been for statistical calculations, and the presentation of experimental stimuli and the automatic collection of timed events (e.g., reaction times, choice-decision times). Here, the traditional capabilities of computers are being exploited - namely, their accurate temporal sequencing, graphical performance, and, above all, their number crunching. As such, they have been powerful and essential tools for those involved in the more psychophysical or cognitive areas of psychology. Computer-based learning (CBL) remains very much a preserve of these more formal domains. The arrival of hypermedia has opened the way for CBL to be exploited within the less formal domains of psychology; but the level of interactivity is usually very restricted, and the constrained presentational styles means that even this technological progression fails to meet the contextual richness needed in the teaching of much of the behavioural sciences. The advent of multimedia has for the first time provided the potential to explore, within the normal undergraduate learning environment, real behaviour using the observational techniques that form the basic methodology of the practising social psychologist.